New variant of PRDM16 gene nucleotide sequence in a family with various phenotypic manifestations of the non-compacted myocardium - R. P. Myasnikov; A. A. Bukaeva; O. V. Kulikova; A. I. Ershova; A. V. Petukhova; E. D. Zotova; A. N. Meshkov; E. A. Mershina; A. V. Kiseleva; M. G. Divashuk; P. S. Pilyus; M. S. Kharlap; et al. (Российский кардиологический журнал)
The article presents the examination of three generations of a family with diagnosed left ventricular noncompaction (LVNC) and various phenotypic manifestations of the disease (isolated, hypertrophic and dilated type of LVNC). As a result of a molecular genetics tests, a previously undescribed single nucleotide deletion in the PRDM16 gene was revealed in all family members with the LVNC phenotype, leading to a frameshift mutation in exon 9 and the formation of a premature termination codon. This gene encodes a transcription factor responsible for after-birth suppressing the expression of genes involved in prenatal and postnatal development. Despite the presence of previous studies showing the relationship of the PRDM16 gene with LVNC development, currently there are insufficient data to prove the pathogenicity of the identified variant. However, the segregation of the symptomatic variant in three generations supports the association of the identified variant with LVNC. With the accumulation of information about changes in PRDM16 in patients with cardiomyopathies, it is possible to change the status of this gene and clarify its contribution to primary heart diseases.